Efficient error detection in multiple way tables. Issue 1 (1st January 2015) - Reviriego, P.; Maestro, J.A.
Abstract : Multiple way tables in which items can be placed on several buckets are used in many computing applications. Some examples are cache memories and multiple hash tables structures. In most cases, the items are stored in electronic memories that are prone to soft errors that can corrupt the stored items. To avoid data corruption, memories can be protected with a parity bit or with an error correction code. It is shown that most single bit errors can be detected in multiple way tables without adding a parity bit. This can be done by placing the items in a predetermined order in the multiple ways of the table.